Pollen harvest features of the Central Amazonian bee Scaptotrigona fulvicutis Moure 1964 (Apidae: Meliponinae), in Brazil - Marques-Souza, Antonio Carlos (Acta Botanica Brasilica, 2020)
Over a twelve-month period, pollen loads transported by Scaptotrigona fulvicutis Moure 1964 were collected from the workers corbiculae right after the hive entrance closure in an area of old secondary forest mixed with some exotic fruit trees and ornamentals. Once the pollen grains were identified, their monthly frequency in the samples and grouping by botanical family established that Mimosaceae, Myrtaceae and Sapindaceae were the most frequently visited. The workers harvested the pollen from 97 plant species distributed in 73 genera and 36 families, mostly: Stryphnodendron guianense (Aubl.) Benth. in April (57,37%) and Schefflera morototoni (Aubl.) Frodin in May (54,73%). The harvested pollen types abundance matrix showed that there was little species dissimilarity between the months, which resulted in the formation of two large groups.